Degradation of Thermally Aged Insulation Paper in Mixed Polyol Ester and Used Mineral Oil - Abdul Rajab; Emilliano Emilliano; Darmawan Hidayat; Mohammad Taufik; Mohamad Kamarol Mohd Jamil; Hidayatul Fadli (LPPM Universitas Andalas, 2026)
This study investigates the mechanical, chemical, and microstructural changes of thermally aged transformer insulation paper in polyol ester and its mixtures with residual used mineral oil. The mixture was intended to simulate retrofilling conditions where complete removal of aged mineral oil from transformers cannot be ideally achieved. The proportions of used mineral oil in the mixtures are 0, 2.5, 5.0, and 7.5% by volume. Kraft paper, cut into approximately 45 cm × 20 cm, was wrapped around 9 g of copper conductor, immersed in about 1000 ml of oil mixture to imitate real transformer conditions. Samples were aged in an oven at 140 °C for 14 and 28 days. The results demonstrate that the chemical and physical integrity of the insulation paper, with tensile strength, FTIR, and SEM analyses consistently indicating increasing cellulose degradation, oxidation, and fiber damage at higher used mineral oil concentrations and longer aging durations. In addition to assessing degradation, the study highlights that hydrolysis of polyol ester generates long-chain fatty acids capable of esterifying cellulose. This reaction contributes to improved paper insulation’s thermal stability by slowing depolymerization and limiting further fiber damage. Conversely, the presence of used mineral oil accelerates cellulose deterioration.